AMP-Activated Protein Kinase Activation in Dorsal Root Ganglion Suppresses mTOR/p70S6K Signaling and Alleviates Painful Radiculopathies in Lumbar Disc Herniation Rat Model. Issue 15 (1st August 2019) - Liu, Yuantong; Li, Jianmin; Li, Hao; Shang, Yue; Guo, Yan; Li, Zhenzhong; Liu, Zhen
Abstract : Study Design: Animal experiment: a rat model of lumbar disc herniation (LDH) induced painful radiculopathies. Objective: To investigate the role and mechanism of AMP-activated protein kinase (AMPK) in dorsal root ganglia (DRG) neurons in LDH-induced painful radiculopathies. Summary of Background Data: Overactivation of multiple pain signals in DRG neurons triggered by LDH is crucial to the development of radicular pain. AMPK is recognized as a cellular energy sensor, as well as a pain sensation modulator, but its function in LDH-induced pain hypersensitivity remains largely unknown. Methods: The LDH rat model was established by autologous nucleus pulposus transplantation into the right lumbar 5 (L5) nerve root. At different time points after AMPK agonist metformin (250 mg/kg/d) or mammalian target of rapamycin (mTOR) inhibitor rapamycin (5 mg/kg) intraperitoneal administration, thermal and mechanical sensitivity were evaluated by measuring paw withdrawal latency (PWL) and 50% paw withdrawal thresholds (PWT). The levels of AMPK, mTOR, and p70S6K phosphorylation were determined by Western blot. We also investigated the proportion of p-AMPK positive neurons in the right L5 DRG neurons using immunofluorescence. Results: LDH evoked persistent thermal hyperalgesia and mechanical allodynia on the ipsilateral paw, as indicated by the decreased PWL and 50% PWT. These pain hypersensitive behaviors were accompanied with significant inhibition of AMPK and activation of mTOR in the associated DRG neurons. Pharmacological activation of AMPK in the DRG neurons not only suppressed mTOR/p70S6K signaling, but also alleviated LDH-induced pain hypersensitive behaviors. Conclusion: We provide a molecular mechanism for the activation of pain signals based on AMPK-mTOR axis, as well as an intervention strategy by targeting AMPK-mTOR axis in LDH-induced painful radiculopathies. Level of Evidence: N/A Abstract : In this study, AMP-activated protein kinase (AMPK) activation by metformin in the dorsal root ganglia neurons not only suppressed mammalian target of rapamycin (mTOR)/p70S6K signaling, but also alleviated lumbar disc herniation (LDH)-induced pain hypersensitive behaviors, which provides experimental evidence for the intervention of LDH-induced painful radiculopathies by targeting the AMPK-mTOR axis.